Study the Effect of Some Growth Factors on the Production of L-Asparaginase Enzyme by Fungal Isolate Aspergillus flavus - Walla H. Shuker (Journal of Global Pharma Technology, 2016)
Nine filamentous fungi from infection fruits and vegetables .Seven isolated were of high productivity for L-Asparaginase enzyme compared with other isolates, this isolates were Aspergillus flavus, A.niger, Pencillium sp., Fusarium sp., Aspergillus flavus was the best isolate for Asparaginase production, depending on diameteron pink colour on the medium plates. Studied the effect of nitrogen and carbon sources, and PH the resulted revealed that the maximum Asparginase production was the following condition: PH 6.0, Glocose as a carbon source, Ammonium sulphate was (121.28) U/100ml.